2007
DOI: 10.1002/chp.138
|View full text |Cite
|
Sign up to set email alerts
|

Adopting health behavior change theory throughout the clinical practice guideline process

Abstract: Adopting a theoretical framework throughout the clinical practice guideline (CPG) process (development, dissemination, implementation, and evaluation) can be useful in systematically identifying, addressing, and explaining behavioral influences impacting CPG uptake and effectiveness. This article argues that using a theoretical framework should increase the utility and probably the implementation of a CPG. A hypothetical scenario is provided using the theory of planned behavior (TPB) to aid in our explanation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 20 publications
1
41
0
1
Order By: Relevance
“…Healthcare providers can make sure that PLWH clearly understand their illness/condition, have an awareness of all treatment options and the relative risks and benefits, and recognize how to navigate the healthcare system to receive the best care possible. 41,42 For example, this may include having providers review rights and privileges, benefits and resources, and any other policies with the patient. New technologies could be used to present this type of information or to administer questionnaires with validated measures relevant to the patients' condition or illness as they are sitting in the waiting area before being seen by their providers.…”
Section: Van Den Berg Et Almentioning
confidence: 99%
“…Healthcare providers can make sure that PLWH clearly understand their illness/condition, have an awareness of all treatment options and the relative risks and benefits, and recognize how to navigate the healthcare system to receive the best care possible. 41,42 For example, this may include having providers review rights and privileges, benefits and resources, and any other policies with the patient. New technologies could be used to present this type of information or to administer questionnaires with validated measures relevant to the patients' condition or illness as they are sitting in the waiting area before being seen by their providers.…”
Section: Van Den Berg Et Almentioning
confidence: 99%
“…Consideration during item development was also given to the theories of DoI and TPB. Some item wording was developed from other similar work (Brouwers et al, 2004;Ceccato et al, 2007;Eccles et al, 2007a;Evans et al, 2006;Francis et al, 2009;Gerrish et al, 2007;Michie et al, 2009;Quiros, Lin, & Larson, 2007;Ramsay et al, 2010;Shiffman et al, 2005). An email invitation to participate in the preevaluation survey was sent to the members of the Network of Pediatric Audiologists of Canada with a link to the e-survey.…”
Section: Survey Instrumentsmentioning
confidence: 99%
“…Evidence has shown that the uptake of knowledge products is, at least in part, a function of the adoptors' perceptions about the attributes of the knowledge product and the process by which the knowledge is developed and translated to clinical practice (Brouwers et al, 2004;Ceccato et al, 2007;Eccles et al, 2007aEccles et al, , 2007bFrancis et al, 2009;Graham et al, 2006;LĂ©garĂ©, 2009;Michie et al, 2009;Ramsay et al, 2010).…”
Section: Acknowledging the Complexity Of Changing Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…TPB has been applied to a number of behaviors in health and social sciences [22,23]. However, its use in predicting application of new knowledge and skills following participation in faculty development programs, especially in the education of health professions, has been extremely limited.…”
Section: Introductionmentioning
confidence: 99%